Authentic leadership: bridging the gap between perception of organizational politics and employee attitudes in public sector museums - Muhammad Asif; Zhiqiang Ma; Mingxing Li; Gang Xie; Weijun Hu (Humanities & Social Sciences Communications)
Abstract In museums’ dynamic and culturally rich environments, employee morale and productivity are crucial for achieving organizational goals. However, employees’ perception of organizational politics can undermine these objectives. Hence, this study investigates the buffering role of authentic leadership in mitigating perceptions of organizational politics and its subsequent effects on organizational citizenship behavior (OCBI and OCBO) and task-oriented performance among museum employees. This research involved 436 employees across six public sector museums in Pakistan, including supervisors and their immediate subordinates. Data were collected in four waves and analyzed using Structural Equation Modeling (SEM). The findings indicate that perceptions of organizational politics significantly negatively influence both organizational citizenship behaviors (OCBI and OCBO) and task-oriented performance. However, authentic leadership buffers these negative effects, significantly reducing perceptions of organizational politics and positively correlated with enhanced task-oriented performance and citizenship behavior. This study highlights the crucial role of authentic leadership in moderating the adverse impacts of organizational politics, fostering a positive work environment in museums, and enhancing both employee productivity and organizational outcomes. The insights from this research offer valuable implications for museum leaders aiming to enhance organizational performance through effective leadership practices.